I︠A︡kornyi︠a︡ mi︠e︡sta Beringovomʺ mori︠e︡ / Izdanīe Gidrograficheskago Departamenta Morskago Ministerstva vʺ 1883 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1883)
Relief shown by hachures. Depths shown by soundings and isolines.; Title translation: Anchorage places on the Bering Sea / published by the Hydrographic Department of the Admiralty in 1883.; Maps translations: Plan of Saint Lawrence Bay (Bering Strait) -- Emma Harbor (Providence Bay) -- Map of Providence Bay (Bering Sea) -- Map of Admiral Butakov Bay in the Bering Sea -- Plan of Vyestnik Bay (on Kamchatka Peninsula) -- Plan Plover roadstead (Providence Bay) -- Plan of Slavyanka Harbor (Plover Bay).; Maps: Planʺ zaliva sv. Lavrentīi︠a︡ (vʺ Beringovom prolivi︠e︡) -- Bukhta Ėmma (vʺ bukhti︠e︡ Providi︠e︡nīi︠a︡) -- Planʺ bukhty Providi︠e︡nīi︠a︡ (vʺ Beringovom mori︠e︡) -- Karta zaliva Admirala Butakova (bukhta Tkachin ili Rtkachin) vʺ Beringovom prolivi︠e︡ -- Plan bukhty Vi︠e︡stnikʺ (na Poluostrovi︠e︡ Kamchatka, u mysa Zheltyĭ) -- Planʺ reĭda Plover (vʺ bukhti︠e︡ Providi︠e︡nīi︠a︡) -- Planʺ Gavani Slavi︠a︡nka (vʺ Bukhti︠e︡ Ploverʺ).; "No. 295" -- bottom right margin Grayscale;